2015
DOI: 10.1002/smll.201503067
|View full text |Cite
|
Sign up to set email alerts
|

Surface Defects Enhanced Visible Light Photocatalytic H2 Production for Zn‐Cd‐S Solid Solution

Abstract: In order to investigate the defect effect on photocatalytic performance of the visible light photocatalyst, Zn-Cd-S solid solution with surface defects is prepared in the hydrazine hydrate. X-ray photoelectron spectra and photoluminescence results confirm the existence of defects, such as sulfur vacancies, interstitial metal, and Zn and Cd in the low valence state on the top surface of solid solutions. The surface defects can be effectively removed by treating with sulfur vapor. The solid solution with surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(117 citation statements)
references
References 35 publications
7
106
0
Order By: Relevance
“…We propose that our findings reflect the dynamic changes in the expression of the multiple intrinsic fungi and fungal genotypes in the different compartments of C. sinensis under the multiple fungi-integrated microecosystem hypothesis [17][18][19]21,[23][24][25][26][27][28]30,33,47], rather than genetic variations under the singlefungus hypothesis [16,29]. Clearly, our interpretation contradicts the hypothesis that the evolutionary distances of O. sinensis are responsible for the differences in the C. sinensis populations in different production areas, which has been proposed by some C. sinensis researchers [38][39]43,45].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…We propose that our findings reflect the dynamic changes in the expression of the multiple intrinsic fungi and fungal genotypes in the different compartments of C. sinensis under the multiple fungi-integrated microecosystem hypothesis [17][18][19]21,[23][24][25][26][27][28]30,33,47], rather than genetic variations under the singlefungus hypothesis [16,29]. Clearly, our interpretation contradicts the hypothesis that the evolutionary distances of O. sinensis are responsible for the differences in the C. sinensis populations in different production areas, which has been proposed by some C. sinensis researchers [38][39]43,45].…”
Section: Discussionmentioning
confidence: 77%
“…No genotyping information to date has been reported for the different conidiogenous structures or for the different conidia discovered in microcycle conidiation of ascospores/conidia studies. Both the macrocosmic RAPD global profiling and microscopic sequencing and morphological findings challenge the hypothesis that C. sinensis is one species of fungus [16,29], but support the hypothesis that C. sinensis is an integrated microecosystem with multiple intrinsic fungi from over 30 genera [17][18][19][21][22][23][24][25][26][27][28]30,33,47]. More and more mycologists have realized that symbiotic interactions between multiple intrinsic fungi in C. sinensis may be the key to the induction of the C. sinensis sexual fruiting body and formation of ascospores, both naturally and in artificial settings, in strict adherence to Koch's postulates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OVs confined in WO 3 achieved a high PC evolution rate, which is ascribed to the promotion of light harvesting due to surface plasmon resonance by the introduction of OVs (Figure e) . Surface defects confined in Zn‐Cd‐S solid solution achieved the outstanding PC hydrogen production rate due to the introduction of sulfur defects by the confirmation of X‐ray photoelectron spectra and photoluminescence spectra . Particularly, Zou et al reported metal‐defected TiO 2 and ZnO semiconductors with abundant metal vacancies, presenting a remarkable PC performance and an essential relationship of the defect structure and the PC performance of metal‐defected photocatalysts.…”
Section: Application Of Defect Engineering For Solar Energy Conversionmentioning
confidence: 93%